Policy in implementation science: Considerations for measurement-based care in the Canadian Armed Forces. - Guérin, Eva; Garber, Bryan; Dowler, Susan T. (Journal of Military, Veteran & Family Health, 2026)
Policy, an intricate and often-overlooked aspect of implementation science (IS), can be leveraged to facilitate the mobilization and uptake of evidence-based practices. However, there are varying conceptualizations of policy in research and practice, and multiple approaches to the policy-making process. This article brings together a selection of literature and current guidance on policy using an IS lens, focusing specifically on the use of policy as an implementation strategy or lever to increase the uptake of interventions and evidence-based practices. The article uses the Canadian Armed Forces' (CAF's) implementation of measurement-based care (MBC) as a case example to discuss IS implications regarding policy. The CAF adopted an MBC system in 2014, coinciding with the consistent evolution of its mental health system. Although MBC is mandatory within the parameters outlined in the current directive (policy), adherence has consistently fallen below target level. The authors provide a brief overview of early implementation milestones for MBC in the CAF and describe the guiding policy in its current form. The authors draw from the IS literature on policy development and implementation, including elements of contextual adaptation and stakeholder consultation, to frame a series of considerations for refining the policy approach to MBC in the CAF. Lay Summary: Measurement-based care refers to regularly assessing patients' perspectives on their symptoms, progress, and outcomes to inform treatment decisions and engage patients in their care. A measurement-based care system has been formally implemented across Canadian Armed Forces (CAF) mental health clinics. Although there is a policy in place that specifies when and how the measurement tools are to be used by mental health care providers in the CAF, there is room for improvement when it comes to adherence. Implementation science is an area of research that focuses on increasing the application of proven intervention or practices by health professionals and policy makers. Within this field, policy can be thought of as a tool or strategy that makes it easier to follow a recommended practice, in this case measurement-based care. Because policy — and policy making more generally — can be incredibly complex and difficult to understand and influence, the aim of this article is to discuss how policy can be developed and used to better support mental health professionals and administrators. The article also offers suggestions for the current CAF policy on measurement-based care.